Penerapan Metode Preference Selection Index untuk Penerima Program Keluarga Harapan di Desa Gunungsari Kabupaten Pandeglang - Hays, Riyan Naufal; Siswanto; Djaksana, Yan Mitha (Jurnal Informatika Universitas Pamulang, 2025)
The Program Keluarga Harapan (PKH) aims to alleviate poverty and improve access to education and healthcare for underprivileged families in Indonesia. In Gunungsari Village, Mandalawangi Subdistrict, Pandeglang Regency, where most residents are low-income farmers and breeders, PKH faces challenges in accurately identifying eligible recipients due to the limitations of manual selection, which is prone to subjectivity and human error. This study explores the application of the Preference Selection Index (PSI) method to improve the objectivity and accuracy of beneficiary targeting. From 973 households, five were selected as a representative sample for manual validation. Twelve socio-economic indicators were used to assess eligibility. The PSI method systematically calculates preference weights across multiple criteria, including income, employment, housing, assets, and infrastructure access, generating a ranking of the most eligible candidates. The highest score obtained was 3.188, identifying Family C as the top candidate. The method showed strong agreement with expert judgment, as evidenced by a Spearman Rank Correlation of 0.9. These findings suggest that PSI enhances the fairness and efficiency of the PKH selection process and supports its digital transformation. This study offers a replicable model for improving governance and targeting in rural social assistance programs.